Memoria Prospectiva: Contexto y Calidad de Compromiso en una Situación de Recuerdo Libre - Martínez Hernández, Ariadna Crisantema; Guevara Sanginés, Martha (Acta Universitaria, 2002)
The memory processes, including recall, are influenced by the objective and logical structure of knowledge, as well as by subjective and motivational aspects. The frequency and distribution of units in a free recall task provide information about the organization of memory and the accesibility of material. The objective of this work was to investigate prospective memory as a function of personality (i. e. selfregulation), goal´s commitment quality (i. e. obligation, intention and desire) and context for which they are generated (i. e. labor and not-labor). Two instruments for free recall of goals were developed and were applied along with Action Control Scale to 70 hotel employees. The results indicate that the self-regulatory tendency, the quality of commitment and the context influence in the amount and structure of remembered goals.
Keywords: Array; Array; Array; Array; Array; Array; Array